Digital employee experience and organizational performance: a study of the telecommunications sector in Oman - Porkodi, S.; Al Balushi, Shahla Said Khamis; Al Balushi, Marwa Khalid Mohammed; Al Hadi, Khulood Othman Rashid; Al Balushi, Zulfa Is’haq Murad (Business, Management and Economics Engineering, 2023)
Purpose – The study aims at assessing the effect of digital employee experience on organisational performance, particularly in the telecommunications sector in the Sultanate of Oman, using quantitative and qualitative analysis. Research methodology – The techniques used in this empirical research include scientific literature analysis, correlation analysis, multiple regression, and sentiment analysis. Findings – The results indicate that organisational performance has a higher association with elements of the digital employee experience like work environment, organisational culture, training availability, technology accessibility, digital tool usability, and leadership support and is statistically significant at the 5% level. Also, 80% of respondents were favourable or indifferent about their digital experience. Research limitations – The study exclusively covers Oman’s telecoms industry and six important digital employee experience elements, so additional factors and industries may be examined further. A direct interview may improve findings since self-reported responses from individuals with demanding work schedules may be biased. Practical implications – Telecommunication companies must increase their efforts to engage employees in the use of digital tools and encourage their employees to utilise the different digital technologies. Originality/Value – The study investigated the six elements of the digital experience of telecom employees and its impact on organisational performance with multiple regression and sentiment analysis.